2022
DOI: 10.3390/brainsci12111480
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence for A Number–Action Mapping in Infancy

Abstract: In the last decades, a growing body of literature has focused on the link between number and action. Many studies conducted on adult participants have provided evidence for a bidirectional influence between numerosity processing and grasping or reaching actions. However, it is not yet clear whether this link is functional in early infancy. Here, we used the event-related potential (ERP) technique to record electrical activity of the brain in response to number–hand pairings. We implemented a cueing paradigm wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…A second set of studies investigated the neuro-cognitive influence of embodied cognition on typical numerical development . Employing EEG in 3-to-4-month-old infants, Decarli et al [ 8 ] found evidence for a neuro-functional link between numerosity processing and hand action processing. With the help of functional near-infrared spectroscopy (fNIRS) in a mental arithmetic training in first graders, Artemenko et al [ 9 ] were able to link the effects of a finger-based training on mental arithmetic (i.e., training-induced facilitation of subbase-5 carry operations) and the activation in the sensorimotor cortex in trained children, suggesting training-induced sensorimotor plasticity in brain development.…”
Section: Typical Numerical Developmentmentioning
confidence: 99%
“…A second set of studies investigated the neuro-cognitive influence of embodied cognition on typical numerical development . Employing EEG in 3-to-4-month-old infants, Decarli et al [ 8 ] found evidence for a neuro-functional link between numerosity processing and hand action processing. With the help of functional near-infrared spectroscopy (fNIRS) in a mental arithmetic training in first graders, Artemenko et al [ 9 ] were able to link the effects of a finger-based training on mental arithmetic (i.e., training-induced facilitation of subbase-5 carry operations) and the activation in the sensorimotor cortex in trained children, suggesting training-induced sensorimotor plasticity in brain development.…”
Section: Typical Numerical Developmentmentioning
confidence: 99%